Innovation technology mediates marketing strategy on the marketing performance of MSMEs - Raihanah Daulay (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
The purpose of this study is to determine the appropriate marketing strategy to improve the performance of MSMEs supported by innovative technology in implementing efficient and effective strategies. This study involved 100 respondents who are MSME actors in Medan City who have been running their businesses for more than one year, using a purposive sampling technique. The research method used is a quantitative method with data analysis using path analysis through the PLS4 application. The test results show that marketing strategy has a significant effect on marketing performance, marketing strategy has a significant effect on innovative technology, and innovative technology has a significant effect on marketing performance. In addition, innovative technology plays a mediating variable in the relationship between marketing strategy and marketing performance of MSMEs in Medan City. The implications of this study indicate that MSMEs need to improve the competitiveness of their products and businesses to be able to optimally seize market opportunities.